Matrix metalloproteinases in the oral fluid as a characteristic of inflammatory-destructive process in periodontal tissues - Samoilenko, A.V.; Titovska, S.O. (Medicni Perspektivi, 2022)
The study of the imbalance between the activity of matrix metalloproteinases and their regulation markers in the oral fluid of patients with generalized periodontitis is necessary for creation of effective methods for early diagnosis and preventive treatment of the disease. The aim of the research was to examine the oral fluid of persons with healthy periodontal tissues, patients with chronic diffuse gingivitis and generalized periodontitis for concentrations of matrix metalloproteinases and their inhibitor, anti- and pro-inflammatory cytokines, markers of bone metabolism and to compare obtained results. 90 persons aged 32-45 years were examined, including 30 persons with intact periodontal tissues, 30 patients with chronic diffuse catarrhal gingivitis and generalized periodontitis of the initial degree and 30 ones with chronic generalized periodontitis of I-II degrees. Periodontal status was assessed using clinical indices and bone mineral density according to computed tomography data. The method of enzyme-linked immunosorbent assay (ELISA) was used to determine the concentration of matrix metalloproteinases MMP-2, MMP-3, MMP-8, MMP-9, MMP-13, tissue inhibitor of metalloproteinases TIMP-1, interleukins-1β, -6 and -4, bone metabolism markers – tartrate-resistant acidic phosphatase and bone alkaline phosphatase, osteocalcin in the oral fluid. The initiation of the inflammatory-destructive process in the periodontal tissues was characterized by an increase levels of MMP and pro-inflammatory IL-1β and IL-6 (р<0.05), a decrease in the concentration of TIMP-1 (р>0.05) and anti-inflammatory IL-4 (р<0.05), against the background of the absence of dynamics of bone metabolism markers in the oral fluid. The progression of the process at the І-II degrees of periodontitis was accompanied by a further increase in the concentration of pro-inflammatory interleukins, an increase in the activity of tartrate-resistant acid phosphatase and a decrease in bone alkaline phosphatase and osteocalcin (р<0.05) in the oral fluid, while the content of MMP did not change (р>0.05). The expression of MMP is important for the preventive diagnosis of generalized periodontitis, but it is not indicative for determining the severity of the disease. The imbalance of MMP and TIMP-1 in the early stages of the pathological process indicates the greatest expediency of using MMP inhibitors in the treatment of patients with gingivitis and periodontitis of the initial degree.